ALLEGORY OF MOMO AS FRACTAL MAPS OF FRAGILE LATIN DEMOCRACIES - Oliveira, Christian Dennys Monteiro de; Paiva, Lizandra Araújo de; Ferreira, Kevin Torres (Geosaberes; Vol 12 (2021)DO - 10.26895/geosaberes.v12i0.1068, 2021)
The present study corresponds to a part of the project Symbolic Spaces of the Latin Carnival: Heritage Mapping of the Theatricality of Tourist Cities. The theme seeks an approach between geometric theory of fractals and the cognitive and conceptual mapping processes. It is intended to explore the possibilities of cultural analysis of allegories, such as scenic structures of carnival parades. The work brings together images from several South American countries in a comparative cultural approach. As the stages of the study show a recreation of faces of the figure of Rei Momo as a catalyst for collective creativity in several carnival cities in the continent. Firstly, by identifying cars and figures in fractal reading, after the conceptual indicators of power. Finally, it deepens comparative reflections regarding this theatricality in Momo's claims, in his South American national contexts.